Katyń - Wajda, Andrzej (Poland : Akson Studio, 2007)
"Katyń" is the name of the forest where the Soviet NKVD forces murdered 15,000 Polish officers, intellectuals and professionals over a 3-day period in 1940 (during which a 14-year-old Wajda lost his own father). Stalin's purpose was to destroy those elements of the population who would be most resistant to Soviet control following WWII. For decades the truth was obfuscated, with the Nazis often blamed for the atrocity. Half a century later, in 1990, Soviet President Mikhail Gorbachev admitted his nation's responsibility. In this film Andrzej Wajda recreates war torn Poland and the stories of both the perpetrators and their victims.
Duration: 01:57:00
Keywords: Fiction films